Isti’adzah Manusia terhadap Jin dalam Al-Qur’an Perspektif Ath-Thabari - Stio, Ahmad Habib (YASIN, 2023)
Isti'adzah is a form of requesting protection from Allah SWT. While in general isti'adzah is ordered to all of His servants aiming to seek protection only from Allah SWT. But there are some people who deviate from seeking protection not from Allah but from the jinn. Therefore researchers are interested in this problem. And this research was conducted aiming to find out why they ask for protection from the jinn while it has been explained in the Koran that asking for protection only from Allah SWT. This study is a qualitative research and the method used is library research. In this discussion, it focuses on human istiadzah towards jinn from the Qur'an and the interpretation of ath-tabari.